2004
DOI: 10.1080/13651820410025110
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder carcinoma: the role of p53 protein overexpression and Ki‐67 antigen expression as prognostic markers

Abstract: p53 protein nuclear overexpression and Ki-67 protein expression in gallbladder carcinoma were not related to histological differentiation, level of gallbladder wall invasion or patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Both the above evidences suggest that squamoid part of adenosquamous cell carcinoma is more aggressive than the adenocarcinoma component. In a study by Hidalgo et al, Ki-67 protein expression in gall bladder carcinoma was not related to histological differentiation, level of GB cancer invasion or patient survival [22].…”
Section: Discussionmentioning
confidence: 87%
“…Both the above evidences suggest that squamoid part of adenosquamous cell carcinoma is more aggressive than the adenocarcinoma component. In a study by Hidalgo et al, Ki-67 protein expression in gall bladder carcinoma was not related to histological differentiation, level of GB cancer invasion or patient survival [22].…”
Section: Discussionmentioning
confidence: 87%
“…Another study by Hidalgo Grau et al . [ 50 ] has not shown any correlation of Ki-67 expression with histological differentiation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…21 In a study conducted by Grau et al on 41 patients of histologically proven cases of GBC, 29 showed p53 poitivity. 22 Roa et al in a study of 157 primary gall bladder carcinoma, found p53 expression in 45% cases. 23 In an Indian study conducted on 78 patients of GBC by Chaube et al p53 positivity was found in only 20% of patients.…”
Section: Discussionmentioning
confidence: 95%